2000
DOI: 10.4269/ajtmh.2000.63.128
|View full text |Cite
|
Sign up to set email alerts
|

IgE deposition in brain microvessels and on parasitized erythrocytes from cerebral malaria patients.

Abstract: Abstract. Postmortem brain tissues of 21 cerebral malaria cases were obtained in Myanmar and Vietnam. The tissues were examined by light microscopy and by an immunohistochemical method. Brain microvessels (capillaries and venules) were examined for the presence of immunoglobulins IgE and IgG, Plasmodium falciparum antigen, and parasitized erythrocytes (PRBC). Deposition of IgE, IgG, and P. falciparum antigen was observed in the microvessels from all specimens examined. Sequestered PRBC in the microvessels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…These observations are contrary to published data describing increased IgE levels that correlate with high concentrations of circulating TNF, a cytokine associated with malaria severity and also with pRBC adherence on brain capillary endothelial cells [9,10,25,26]. The results suggest that either IgE does not play an important role in CM pathogenesis, or that these antibodies may participate in the parasite sequestration into the brain or other organ capillaries [24]. …”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…These observations are contrary to published data describing increased IgE levels that correlate with high concentrations of circulating TNF, a cytokine associated with malaria severity and also with pRBC adherence on brain capillary endothelial cells [9,10,25,26]. The results suggest that either IgE does not play an important role in CM pathogenesis, or that these antibodies may participate in the parasite sequestration into the brain or other organ capillaries [24]. …”
Section: Discussioncontrasting
confidence: 93%
“…Nevertheless, it was reported that IgE levels were greatest in patients developing severe disease than in CM group (Figure 1A and 1B). When considering the percentage of patients that produce high levels of IgE per group, it was shown that IgE levels are higher in UM and SM (Figure 1C and 1D) than in CM patients who had values similar to that of the controls [8,24]. In addition, the median levels of circulating IgE in the ExCM group were close to that of the CM group.…”
Section: Discussionmentioning
confidence: 67%
“…Increased IgE levels were detected in some lupus patients (58), and IgE deposits found in ϳ10% of cases in human renal disease were correlated with bad prognosis (59 -63). Similarly, diseases related to parasite infections might involve IgE immune deposits (64,65). HgCl 2 -induced allergic reactions have been associated with increased IgE production (66) In addition, there is a role for IgE deposits in Wegener's granulomatosis, as well as IgE myelomas (67,68).…”
Section: Autoimmune Nephritismentioning
confidence: 99%
“…If IFN-g and interleukin 12 (IL-12) have significant protective effects against SM [10,11], then cytokines that inhibit Th1 cell differentiation or that interfere with IFN-g-mediated activation of phagocytes-such as interleukin 10 and interleukin 4 (IL-4)-may increase the risk of SM. Indeed, children with SM have elevated immunoglobulin E (IgE) levels, and IgE deposits have been observed in brain vessels in which massive sequestration had occurred [12,13].…”
mentioning
confidence: 99%